CONSTRUCTION OF TRANSFER FUNCTIONS AS A DRYING PROCESS CONTROL OBJECT - Xusanov, Suban (Innovatsion texnologiyalar, 2024)
The purpose of modeling in the development of a model of a drying process control object is presented in the article. Approximation of the transition characteristic in the control channels, obtaining the transfer functions of the object on all the main channels of the influence transmission, the Simoyu method was used. Taking into account the fact that the main channels of the object under study have significant inertia and delay, as well as its dynamic properties, transfer functions with sufficient accuracy are proposed. The proposed mathematical model of the drying process allows for the synthesis of adaptive control laws for the considered process.